The demographical analysis of COVID-19 in the South western province of Pakistan, an approach to analysing its low mortality rates - Zarak, Muhammad Samsoor; Arshad, Zara; Khan, Sarmad Saeed; Tareen, Abdul Sami; Kakar, Saliha; Sana, Hamaiyal; Tareen, Helmand Khan; Nithikathkul, Choosak (International Journal Of Community Medicine And Public Health, 2020)
Background: COVID-19 cases are exponentially surging around the globe. At the time of study, Pakistan had 7,993 cases and 159 deaths. Out of these positive cases, 432 cases were from Baluchistan. Baluchistan being the South western province of Pakistan; is the basin of the first contact of the virus in Pakistan. Methods: A retrospective study was conducted where data was included from the very first tested case up till 19th April 2020. A total data of 432 patients were acquired and analyzed using SPSS version 20. Results: The proportion of males was 308 (71.3%), belonging to the middle age group 21-30 years (23.4%, n=101). Contrary to popular belief, 60.6% (n=262) of these cases had been infected by local spread, while only 28.9% (n=125) were pilgrims (Zaireen) returning from Iran. Moreover, 146 (33.8%) cases have been reported in just the last five days of acquired data. Quetta and Loralai have displayed the highest COVID-19 attack rate of 14 among all the other districts. Furthermore, the mortality rate was 1.15% and all cases were of age above 40 years. Conclusions: There has been a rapid surge in several cases in Baluchistan, as portrayed herein. While this study depicts a fair picture of the COVID-19 demographic trend, the study has clear indications for the provincial, local spread that have been realized by this data along with a spike in cases in the last few days, which is maybe due to non-compliance to physical distancing rules.